45.0k views
2 votes
4(m-9)=2(2m+1)-40
What is the answer

User Besil
by
5.4k points

1 Answer

3 votes

Answer: i think that's right if not than t don't have a solution

Step-by-step explanation:4(m−9)=2(2m+1)−40

(4)(m)+(4)(−9)=(2)(2m)+(2)(1)+−40(Distribute)

4m+−36=4m+2+−40

4m−36=(4m)+(2+−40)(Combine Like Terms)

4m−36=4m+−38

4m−36=4m−38

Step 2: Subtract 4m from both sides.

4m−36−4m=4m−38−4m

−36=−38

Step 3: Add 36 to both sides.

−36+36=−38+36

0=−2

User Lsp
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.